Identification and Delineation of Potential Large-scale Landslide-prone Areas Along National Highway 32, Lao Cai Province, Vietnam - Thi Toan, Dương; Khang, Dang Quang; Dung, Tran Thi; Duc, Do Minh (VNU Journal of Science: Earth and Environmental Sciences, 2025)
In recent years, large-scale landslides have occurred with increasing frequency, causing substantial socio-economic and human losses. This study presents a preliminary identification and delineation of areas susceptible to large-scale landslides along National Highway 32 (QL32), from Khau Pha Pass to Khao Mang Commune, Lao Cai Province, Vietnam. By integrating geological–geotechnical surveys, unmanned aerial vehicle (UAV) image analysis, and statistical methods, the study delineated 24 potential large-scale landslide sites. These sites are categorized into two main types: i) Cluster landslides (2/24); and ii) large and deep-seated landslides (22/24), each with an estimated volume exceeding 3000 m³. Cluster landslides typically occur within the same watershed where significant elevation differences exist and are often triggered by extreme rainfall. Large and deep-seated landslides are commonly associated with concave slope topography, thick weathered soil (>5 m), heterogeneous slip surfaces, ground cracks or subsidence, and the loss of paddy field cultivation due to active sliding that prevents water retention within cracks. These characteristics represent critical diagnostic indicators identified in the study area, which may help local communities recognize potential large-scale landslide hazards. The findings provide fundamental insights into the typical signs of large-scale landslides, thereby supporting local awareness, establishing a basis for early warning systems, and contributing to timely responses and risk mitigation.